2021
DOI: 10.1088/1755-1315/832/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Rainfall Data by The GPM Satellite (Case Study at Sriwijaya University, Indralaya)

Abstract: The problem in obtaining rainfall data information is that the measurement results of rainfall from the measuring station are not recorded and areas are difficult to reach to measure rainfall directly. Lack of data availability and continuity of rainfall data is one of the obstacles in obtaining climatological information in South Sumatra. GPM satellites (Global Precipitation Measurement) need to be researched in order to overcome obstacles in obtaining rainfall measurement data in an area. This study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Monthly rainfall data is validated by calculating the bias parameter [2], [16]. Data validation is carried out to prove whether a process or method can produce consistent results by predetermined specifications [6]. Data validation before and after calibration will be carried out using three statistical parameters, namely correlation coefficient (r), Root Mean Square Error (RMSE), and Mean Absolute Error (MAE).…”
Section: Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…Monthly rainfall data is validated by calculating the bias parameter [2], [16]. Data validation is carried out to prove whether a process or method can produce consistent results by predetermined specifications [6]. Data validation before and after calibration will be carried out using three statistical parameters, namely correlation coefficient (r), Root Mean Square Error (RMSE), and Mean Absolute Error (MAE).…”
Section: Validationmentioning
confidence: 99%
“…This will decrease the data accuracy variable because rainfall is strongly influenced by space and time. One of the areas experiencing this problem is South Sumatra, where in some areas, it is difficult to obtain sufficient and sustainable rainfall data [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Indonesia, [13], [14], [15], [16], [17], [18], [19], and [20] have also conducted the same study. Especially for the island of Sumatra, [21], [22], [23], and [24] showed that GPM IMERG is one of the possible rainfall satellite data that can be used in imitating the ground station data.…”
Section: Introductionmentioning
confidence: 99%